2022
DOI: 10.3390/bios12090739
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the “Antigen Hook Effect” in Lateral Flow Sandwich Immunoassay: The Case of Lumpy Skin Disease Virus Detection

Abstract: Lumpy skin disease (LSD) is an infectious disease affecting bovine with severe symptomatology. The implementation of effective control strategies to prevent infection outbreak requires rapid diagnostic tools. Two monoclonal antibodies (mAbs), targeting different epitopes of the LSDV structural protein p32, and gold nanoparticles (AuNPs) were used to set up a colorimetric sandwich-type lateral flow immunoassay (LFIA). Combinations including one or two mAbs, used either as the capture or detection reagent, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
(33 reference statements)
3
15
0
Order By: Relevance
“…The gold standard for diagnosing LSD virus is virus isolation, however using this method requires time to isolate and culture the virus from tissue or chorioallantoic membranes from embryonated chicken eggs (Amin et al, 2021). This is in accordance with the statement of Cavalera et al (2022) which stated that virus isolation is the gold standard for diagnosing LSD, but it takes several weeks to isolate the virus. However, according to the World Organization for Animal Health (WOAH) recommends using the VNT method as the gold standard in detecting antibodies to the LSD virus.…”
Section: Diagnosissupporting
confidence: 90%
“…The gold standard for diagnosing LSD virus is virus isolation, however using this method requires time to isolate and culture the virus from tissue or chorioallantoic membranes from embryonated chicken eggs (Amin et al, 2021). This is in accordance with the statement of Cavalera et al (2022) which stated that virus isolation is the gold standard for diagnosing LSD, but it takes several weeks to isolate the virus. However, according to the World Organization for Animal Health (WOAH) recommends using the VNT method as the gold standard in detecting antibodies to the LSD virus.…”
Section: Diagnosissupporting
confidence: 90%
“…In cases where the test line was visualized but with the faint control line, the antigen could be causing steric hindrance, blocking the binding site for the immobilized secondary antibody of the control line. The kinetics of solid-phase immobilized antibodies have demonstrated that equilibrium between antigen, capture and detection antibodies do not occur simultaneously, suggesting that steric hindrance plays a role in the detection-antigen-capture sandwich formation [ 22 ]. However in some instances, antibodies are able to re-organize to allow for further binding, and a high binding affinity may prevent this re-organization, causing saturation of binding sites at a faster rate [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of solid-phase immobilized antibodies have demonstrated that equilibrium between antigen, capture and detection antibodies do not occur simultaneously, suggesting that steric hindrance plays a role in the detection-antigen-capture sandwich formation [ 22 ]. However in some instances, antibodies are able to re-organize to allow for further binding, and a high binding affinity may prevent this re-organization, causing saturation of binding sites at a faster rate [ 22 , 23 , 24 ]. Thus, in addition to target epitope compatibility, the association (k ass ) and dissociation (k off ) rate constants of the detection and capture antibodies may have a crucial role in defining suitable binding pairs.…”
Section: Discussionmentioning
confidence: 99%
“…There is no cross-reactivity with other common bovine viruses ( Jiang et al, 2022 ). A rapid diagnostic tool of colorimetric sandwich-type lateral flow immunoassay (LFIA) was established using two monoclonal antibodies against different epitopes of P32 structural protein of LSDV and gold nanoparticles ( Cavalera et al, 2022 ). The sensitivity of this new method is similar to that of ELISA, but it has not been widely used in clinical diagnosis, and its specificity needs to be determined after clinical trials.…”
Section: Research Advances On the Diagnostic Methods Of Lsdmentioning
confidence: 99%